Educating adults towards color blind diagnostic among children through poster awareness campaign / Intan Nur Firdaus Muhammad Fuad, Sharifah Raudzah S. Mahadi & Nur Hisham Ibrahim - Intan Nur Firdaus, Muhammad Fuad; Sharifah Raudzah, S. Mahadi; Nur Hisham, Ibrahim (Universiti Teknologi MARA, Perak, 2017)
To identify whether a person has a color blind deficiency a test commonly used for this detection is Ishihara test, where the dots of the various colors are combined to form an object, letters or numbers. These tests are normally found in hospitals or institutions where patients undergo the test. Assimilation of skills needed to interpret the objects, letters or numbers are required to specify whether the person has a color vision problem.1 The development of children's language can be seen in terms of the ability to receive, understand and produce. Children as early as one year often possess limited skills in interpreting objects but are difficult to interpret letters and numbers. Among the objects that can be interpreted by children are commonly surrounded by their environment and that repeat for the child to remember. It is known as cognitive (mental activity) of Jean Piaget's theory.2 (The process of increasing capability of thought, knowledge and intellectual. The ability to form and generate a lot of common sense to solve problems, understand and analyze.) Ishihara Test specifically builds for adults who are not illiterate. Been aware on that issues Dr. Terrace L. Wagoner test the process by making it easier to generate the image of the objects around that is easily been recognize by children. For example like ball, apple, star and etc., in the form of dots of color. Dr. Terrace test also has been approved by a number of ophthalmologists. These test however, only suitable for children aged 3 years and above. 3 In Malaysia colorblind issue among kids are not commonly been discussed. Rarely do we see Malaysian society, especially parents concerned about this issue. Mostly color blindness is only detected when they are starting out to express their opinions and their feelings. Parents and educators that are not been educating by this inability, will make their children face this disabilities to deal with it themselves.